2016
DOI: 10.1016/j.jth.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Active commuting to school in Portuguese adolescents: Using PALMS to detect trips

Abstract: The declining levels of physical activity (PA) have led to active commuting to school (ACS) being seen as a key strategy to increase PA levels in school-aged children. In Portugal, no data exists on the patterns of this behavior, an essential step for developing evidence-based and effective interventions. The purpose of this study is to explore the travel to school behavior using an objective methodology. Methods: 155 adolescents (mean age 15.9±1.1 years) wore an accelerometer and a GPS for 7 consecutive days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 35 publications
6
37
1
4
Order By: Relevance
“…The current study indicates that just below half of the participants (47.3%) engaged in ATS from home to school, which corroborates other studies on Chinese [21,22] and North American samples [34,35]. Regardless, in contrast with studies of European countries [36,37], the adolescents in our study showed reduced ATS performance. Inconsistencies in the ATS levels between our study other research are primarily due to different measures used.…”
Section: Interpretations Of Ndingssupporting
confidence: 88%
“…The current study indicates that just below half of the participants (47.3%) engaged in ATS from home to school, which corroborates other studies on Chinese [21,22] and North American samples [34,35]. Regardless, in contrast with studies of European countries [36,37], the adolescents in our study showed reduced ATS performance. Inconsistencies in the ATS levels between our study other research are primarily due to different measures used.…”
Section: Interpretations Of Ndingssupporting
confidence: 88%
“…Many focussed exclusively on MVPA within the active transportation environment, specifically the commute toand-from school. 47,55,59,60 Collins et al 47 in their study of youth from England found that active commuting contributed to 35% of daily MVPA. Commuting distance appears to be a significant predictor of active transportation, with active commuters often living closer to the destination than passive commuters.…”
Section: Table 2 (Continued) Included Study Characteristics and Summamentioning
confidence: 99%
“…MVPA was the most studied behaviour. There are a total of 22 studies in children, 17 in youth [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] and 20 in adults. 28, [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] Sample sizes ranged from 12 to 1053; 39% were small (N ≤ 100).…”
Section: Risk Of Bias Appraisalmentioning
confidence: 99%
See 1 more Smart Citation
“…Les localisations le plus souvent mention nées à propos des adolescents étaient le domicile, l'école, les installations de loisirs, le transport actif et les espaces verts. Bon nombre d'adolescents pratiquaient exclu sivement une APMV en lien avec le trans port actif, pour aller à l'école et en revenir 47,55,59,60 80 . Chez les enfants et les adolescents, les don nées probantes vont dans le sens d'une corrélation positive entre l'accès à des installations de loisirs, des terrains de jeux et des parcs, les mesures de l'accessibilité piétonnière (en particulier les trottoirs) et l'AP 80,81 .…”
Section: Résultats Liés à La Localisation Chez Les Adolescents (12 à unclassified